Level of knowledge about neonatal danger signs and associated factors among postpartum mothers in public hospitals, northeastern Ethiopia - Muluken Amare Wudu; Yemane Eshetu Bekalu; Tarikua Afework Birehanu; Dagne Belete Gebrye; Molla Kassa Hailu (Elsevier, 2024)
Background: Knowing and seeking medical attention for neonatal danger signs has many benefits for reducing neonatal morbidity and death. Despite numerous interventions that have been made to raise mothers' awareness about neonatal danger signs, the desired level of knowledge has not yet been reached in Ethiopia. Objective: To assess the level of knowledge of neonatal danger signs and associated factors among postpartum mothers in public hospitals in the Eastern Amhara region, northeastern Ethiopia. Methods: A hospital-based cross-sectional study was conducted in four government hospitals between January 10, 2023, and February 10, 2023.421 participants in the study were selected using a systematic random sampling technique. Face-to-face interviews, observation, and chart reviews were used to collect the data. The association was discovered through multivariate logistic regression analysis. Result: Only 36.6% (154) of mothers were knowledgeable about newborn danger signs in this study. Mothers who had higher institution status [(adjusted odds ratio) AOR = 3.355, 95% CI (1.751, 6.428)]; who were civil servants or a private employer [AOR = 2.986, 95% CI (1.822, 4.892)] and [AOR = 2.544, 95% CI (1.269, 5.138)]; and who had counseling about breastfeeding [AOR = 2.614, 95% CI (1.695, 4.029)] were positive predictors of awareness of neonatal danger signs. Conclusion: In this study, the level of mothers' awareness of newborn danger signs was low and required more effort. Moreover, mothers who were educated, worked as civil servants or private employers, had a family size of 4-6, and received breastfeeding counseling were linked to mothers' good awareness of newborn danger signs. As a result, intensive community and facility-based health promotion activities on newborn danger signs should be strengthened, with special emphasis on uneducated and housewife mothers and breastfeeding counseling sessions.